Development of Science E-Worksheet Based on Socio Scientific Issues on the Human Respiratory System - Meilani, Nisa; Pusporini, Widowati; Setyawan*, Dhimas Nur; Kuncoro, Krida Singgih; Poort, Elang Amadious; Sain, Zohaib Hassan (Jurnal IPA & Pembelajaran IPA, 2025)
Learning in schools still tends to be teacher-centered, with student worksheets often being overly simplistic. Additionally, students generally prefer kinesthetic learning activities. To address this, we developed an electronic student worksheet (e-worksheet) based on socio-scientific issues (SSI) for the human respiratory system topic using a design-based research (DBR) approach. This study aimed to: (1) design and iteratively refine the SSI-based E- Worksheet through expert collaboration and user testing; (2) evaluate its feasibility; and (3) explore student responses. Conducted in a private junior high school in Yogyakarta, the DBR process involved four interconnected phases: problem analysis (interviews with teachers and classroom observations), prototype design, implementation cycles (with 10 and 77 students respectively), and reflective evaluation. Data were collected from science education experts, teachers, and eighth-grade students through observations, interviews, and questionnaires, then analyzed descriptively. Results indicate that the DBR process successfully produced a contextually grounded e-worksheet, rated highly feasible by experts (content suitability: 86%, graphics: 82%) and teachers. Student responses showed strong approval (85% relevance perception, 82% engagement increase), confirming its suitability for supporting science learning